Pertumbuhan dan produksi tanaman kacang tanah (Arachis hypogaea l.) dengan inokulasi cendawan mikoriza vesikular-arbuskular dan pemupukan fosfat - Disna Afina Faza; Dwi Retno Lukiwati; Karno Karno (Journal of Agro Complex, 2019)
ABSTRACT  The objective of this research was to study the growth and production of peanut at phosphate fertilization and vesicular-arbuscular mycorrhizal fungi (MVA) inoculation. This research was conducted in green house and Laboratory of Plant Physiology and Breeding UNDIP, and Laboratory of Micology UGM from April 16th to August 15th 2017. The research was assigned in completely randomized factorial design with the first factor was the phosphate fertilization control, Triple Super Phosphate (TSP) and rock phosphate (BP) and second factor was without vesicular-arbuscular mycorrhizal fungi (MVA) inoculation and with vesicular-arbuscular mycorrhizal fungi (MVA) inoculation. The results showed that TSP fertilizationhad significant effect onplant height, number of pods, weight of pods, weight of seed and total P content of soil. Fertilization of BP had significant effect onnumber of pods, weight of pods, weight of seed, total P content of soil and total P of peanut hay. Inoculation of MVA had significant effect onplant height, number of pods, weight of pods, weight of seed, total P content of soil, percentage of colonization on plant roots and number of MVA spores.Keyword: peanut, vesicular-arbuscular mycorrhizal fungi, phosphorus fertilization ABSTRAK Penelitian bertujuan untuk mengkaji pertumbuhan dan produksi tanaman kacang tanah (Arachis hypogaea L.) pada berbagai jenis pemupukan fosfat dan inokulasi cendawan mikoriza vesikular-arbuskular (MVA). Penelitian dilakukan pada tanggal 16 April – 15 Agustus 2017 di green house dan Laboratorium Fisiologi dan Pemuliaan Tanaman UNDIP, serta Laboratorium Mikologi UGM. Penelitian disusun dengan rancangan acak lengkap faktorial dengan faktor pertama adalah kontrol, pemupukan Triple Super Phosphate (TSP), Batuan Fosfat (BP) dan faktor kedua adalah tanpa inokulasi cendawan MVA dan dengan inokulasi cendawan MVA. Hasil penelitian menunjukkan bahwa perlakuan pemupukan TSP berpengaruh nyata terhadap tinggi tanaman, jumlah polong, bobot polong, bobot biji dan kadar P total tanah. Pemupukan BP berpengaruh nyata terhadap jumlah polong, bobot polong, bobot biji, kadar P total tanah dan kandungan P jerami tanaman kacang tanah. Inokulasi cendawan MVA berpengaruh nyata terhadap tinggi tanaman, jumlah polong, bobot polong, bobot biji, kadar P total tanah, persentase kolonisasi pada akar tanaman dan jumlah spora cendawan MVA.Kata kunci: kacang tanah, cendawan mikoriza vesikular-aruskular, pemupukan fosfat